2022
DOI: 10.1186/s42358-022-00238-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peripheral neuropathy in lower limbs of patients with rheumatoid arthritis and its relation to fall risk

Abstract: Background Rheumatoid Arthritis (RA) is a chronic disabling systemic disease characterized by joint inflammation, and extra-articular manifestations, including peripheral neuropathy, a condition that can be associated with changes in muscle strength, proprioception and postural balance contributing for the risk of falls. The objective of this study is to analyze the incidence of peripheral neuropathy in patients with RA and its association with the occurrence of falls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
2
2
0
Order By: Relevance
“…A significant majority, 70% (105 individuals), reported experiencing considerable difficulty in performing daily activities, highlighting the debilitating impact of lower extremity arthritis on their functional capacity. Moreover, an overwhelming 80% (120 individuals) of the study cohort expressed a fear of falling, a concern that significantly outweighs the 20% (30 individuals) who did not share this fear (16,21). These findings align with existing literature that underscores the intricate relationship between arthritis in the lower extremities and an increased risk of falls among the elderly.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A significant majority, 70% (105 individuals), reported experiencing considerable difficulty in performing daily activities, highlighting the debilitating impact of lower extremity arthritis on their functional capacity. Moreover, an overwhelming 80% (120 individuals) of the study cohort expressed a fear of falling, a concern that significantly outweighs the 20% (30 individuals) who did not share this fear (16,21). These findings align with existing literature that underscores the intricate relationship between arthritis in the lower extremities and an increased risk of falls among the elderly.…”
Section: Discussionsupporting
confidence: 81%
“…Given the high prevalence of lower limb arthritis among the elderly and its direct correlation with discomfort, reduced functionality, and disability, a thorough understanding of its impact on physical function and fall risk is indispensable (5,6). This knowledge is pivotal in devising targeted interventions aimed at mitigating these risks and enhancing the quality of life for this vulnerable population segment (10,16).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, other large studies of cancer overall have also shown no increased (20,43,44) or net decreased risk of cancer (45). Finally, the presence of an association between several comorbidities and RA in this study served as a reassuring positive control given established connections from RA literature including asthma (46), COPD (47), CAD (48), GERD and thyroid disease (20), ILD (49), obesity (18), and neuropathy, including vasculitic neuropathy (50), peripheral neuropathy (51), and carpal tunnel syndrome (52).…”
Section: Discussionsupporting
confidence: 47%
“…The existing literature underscores the importance of comprehensive treatment approaches in RA, emphasizing the need for interventions that not only control disease activity but also address functional impairments and quality of life. However, there is a gap in understanding how combined therapeutic modalities can optimize these outcomes, particularly in the context of RA with concurrent PN (10)(11)(12). This research aims to fill the identified gap by comparing the effectiveness of combined NMES and DMARD therapy versus DMARD therapy alone in enhancing gait and reducing fall risks in RA patients with PN.…”
Section: Introductionmentioning
confidence: 99%